2009
DOI: 10.1111/j.1529-8817.2009.00760.x
|View full text |Cite
|
Sign up to set email alerts
|

TAXONOMIC REVISION OF SARGASSUM SPECIES (FUCALES, PHAEOPHYCEAE) FROM NEW CALEDONIA BASED ON MORPHOLOGICAL AND MOLECULAR ANALYSES1

Abstract: Sargassum C. Agardh (1820) is a taxonomically difficult genus distributed worldwide and reported as the most species-rich genus of the Fucales. It is especially abundant in the Pacific where decreasing species richness is reported to occur from west to east. New Caledonia has been recognized as one of the hotspots of Sargassum diversity; however, species lists available for this region are old and incomplete and have not yet been updated with regard to the latest taxonomic revisions published. This study aimed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
13
0
1

Year Published

2010
2010
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(15 citation statements)
references
References 40 publications
1
13
0
1
Order By: Relevance
“…Specifically, we preferred sequences generated in the recent Sargassum ‐focused taxonomic work by Mattio et al. (, , , , , 2010), Mattio and Payri (), followed by sequences from other published studies (Camacho et al ) and, lastly, unpublished sequences uploaded by taxonomists. After this screening process, data were found to be available for 99 species, representing 28% of all valid Sargassum species (Guiry and Guiry ).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Specifically, we preferred sequences generated in the recent Sargassum ‐focused taxonomic work by Mattio et al. (, , , , , 2010), Mattio and Payri (), followed by sequences from other published studies (Camacho et al ) and, lastly, unpublished sequences uploaded by taxonomists. After this screening process, data were found to be available for 99 species, representing 28% of all valid Sargassum species (Guiry and Guiry ).…”
Section: Methodsmentioning
confidence: 99%
“…Recent availability of DNA sequence data for a large number of Sargassum species has improved our understanding of phylogenetic relationships within the group (Mattio et al. , , , Mattio and Payri , Yip et al. ).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Womersley (1954) proposed to regard S. boryi and Sargassum scabripes J. Agardh as heterotypic synonyms of S. peronii and S. decurrens , respectively. However, Mattio and Payri (2009) examined type material and morphological variability and concluded that S. boryi should be regarded as a synonym of S. decurrens and not of S. peronii . It is proposed here to designate S. decurrens as the type species of the reinstated genus Sargassopsis .…”
mentioning
confidence: 99%
“…2004, Mattio et al. 2008, 2009, 2010, Mattio and Payri 2009). The reinstatement of Sargassopsis by Draisma et al.…”
mentioning
confidence: 99%